Cholinesterase activity in serum during general anesthesia in patients with or without vascular disease - Yitzhak Brzezinski-Sinai (Nature Portfolio, 2021)
Abstract Maintaining hemodynamic stability during the induction and maintenance of anesthesia is one of the challenges of the anesthesiologist. Patients with vascular disease are at increased risk of instability due to imbalance between the sympathetic and parasympathetic parts of the autonomic nervous system, a balance accessible by serum cholinesterase activity. We aim to characterize the dynamics of cholinesterase activity in patients undergoing general anesthesia (GA) and surgery. This was a prospective study of 57 patients undergoing ambulatory or vascular surgery under GA. Cholinesterase activity was measured before the induction of anesthesia, after 15 min and at the end of surgery by calculating the capacity of serum acetylcholinesterase (AChE) and butyrylcholinesterase to hydrolyze AcetylThioCholine. Data on atherosclerotic disease, anesthesia management were analyzed. Both AChE and total cholinergic status (CS) decreased significantly after GA induction at 15 min and even more so by the end of surgery. Vascular surgery patients had lower baseline cholinesterase activity compared to ambulatory surgery patients. Patients requiring intraoperative administration of phenylephrine for hemodynamic support (21.1%) had a significantly lower level of AChE and CS compared to untreated patients. Our findings serve as a mirror to the sympathetic/parasympathetic imbalance during GA, with a marked decrease in the parasympathetic tone. The data of a subgroup analysis show a correlation between low cholinesterase activity and an increase in the need for hemodynamic support.